2013
DOI: 10.1016/j.pcl.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Infectious Diseases

Abstract: Synopsis Neonatal sepsis remains a feared cause of morbidity and mortality in the neonatal period. Maternal, neonatal and environmental factors are associated with risk of infection, and a combination of prevention strategies, judicious neonatal evaluation and early initiation of therapy are required to prevent adverse outcomes. The following chapter reviews recent trends in epidemiology, and provides an update on risk factors, diagnostic methods and management of neonatal sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
143
0
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(177 citation statements)
references
References 137 publications
4
143
0
15
Order By: Relevance
“…[3] CRP was first described in the 1930's and since then multiple studies have shown elevation of the CRP in several infectious and non-infectious etiologies that share a common background of inflammation or tissue injury. [4] Presepsin (sCD14 st) is a trunked portion of soluble CD14, released by shedding from the surface of many immune cells, such as macrophages, monocytes, and neutrophils, after being stimulated by pathogens. Presepsin has recently been described as a reliable diagnostic and prognostic marker of sepsis.…”
mentioning
confidence: 99%
“…[3] CRP was first described in the 1930's and since then multiple studies have shown elevation of the CRP in several infectious and non-infectious etiologies that share a common background of inflammation or tissue injury. [4] Presepsin (sCD14 st) is a trunked portion of soluble CD14, released by shedding from the surface of many immune cells, such as macrophages, monocytes, and neutrophils, after being stimulated by pathogens. Presepsin has recently been described as a reliable diagnostic and prognostic marker of sepsis.…”
mentioning
confidence: 99%
“…treptococcus agalactiae, usually termed group B streptococcus (GBS), is one of the most important causes of early-onset neonatal infection (1,2). The incidence of neonatal GBS infection ranges from 0.80 to 3.06 per 1,000 live births in developing countries (1).…”
mentioning
confidence: 99%
“…Sepsis is a major cause of morbidity and mortality in NBs, despite advances in intensive care 23,24 . It is believed that the severity of the clinical evolution of sepsis is due to several factors, such as prematurity and varying degrees of defi ciencies in the innate and adaptive immune responses [25][26][27] , which affect the interaction between the host and the infectious agent with, consequently, an impact on the cascade of events comprising the immune response.…”
Section: Discussionmentioning
confidence: 99%